Parenting dimensions and hardiness personality in Muslim university students - Safira, Diana; Afriani, Afriani; Mawarpury, Marty; Sulistyani, Arum (INSPIRA: Indonesian Journal of Psychological Research, 2024)
The objective of this study is to examine the relationship between parenting dimensions and hardiness personality in university students. This research employs a quantitative design involving 367 students aged 18-21 from four universities in Banda Aceh, selected using Multistage Cluster Sampling and Disproportionate Stratified Random Sampling techniques. The hypothesis testing in this study employs Pearson Product Moment Correlation. The results indicate correlation coefficients of r = .229 (p < .05) for the warmth dimension, r = -.189 (p < 0.05) for the rejection dimension, r = .319 (p < .05) for the structure dimension, r = -.123 (p < .05) for the chaos dimension, r = .407 (p < .05) for autonomy support, and r = -.007 (p > 0.05) for the coercion dimension. The findings of this study suggest that an increase in the warmth, structure, and autonomy support dimensions is associated with an increase in hardiness personality. However, an increase in the rejection and chaos parenting dimensions is associated with a decrease in hardiness personality. The coercion dimension was found to have no relationship with a hardy personality. This study demonstrates that implementing positive parenting dimensions by parents can enhance the hardiness personality among students. Furthermore, it offers insights for higher education institutions to develop psychological support programs and soft skills training that can assist students in fostering a hardiness personality.